Analisis Tingkat Kesehatan Bank dengan Metode RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) Pada PT. Bank Jago Tbk Periode 2019 – 2021 - Apriana Anggreini Bangun; Wuri Purnamasari; Gita Asti Diah aprilia (Journal Of Business, Finance, and Economics (JBFE), 2023)
The Bank's soundness level is one of the important aspects in the banking world to maintain and protect public trust, thus the bank's soundness level must be maintained and maintained. The purpose of this research is to analyze the soundness level of PT Bank Jago, Tbk using the RGEC method for the 2019-2021 period. The type of data used in this study is secondary data sourced from the Annual Financial Report of PT Bank Jago, Tbk. The results of this research show that PT Bnak Jago, Tbk for the 2019-2021 period in terms of Risk Profile using credit risk gets a very healthy predicate and using liquidity risk gets a fairly healthy predicate, in terms of Good Corporate Governance gets a healthy predicate, in terms of Earnings using ROA and ROE get unhealthy predicate and using NIM get healthy predicate, in terms of Capital get very healthy predicate, and in terms of RGEC aspect get pretty healthy predicate.